Development Of A Methodology To Enhance Design For Assembly - -, Rahmatullah (2005)
Assembly is the activity in which the activities of design, engineering, manufacturing, and logistics are brought together to create an object that performs a function. Design for Assembly (DFA) is an approach that addresses product structure simplification, where the total number of parts in a product is a key indicator of product assembly quality. The objective of this research is to develop a methodology to help the designer improve product design and development. The two main concepts that are central to the development of Design for Assembly (DFA) method are firstly how to make enhancement of DFA, and secondly how to develop an evaluation system for DFA. The enhancement of DFA is characterized by a robust procedure to improve product design. a reliable method to solve problems in design for assembly activities and the ability to increase ideas in product design. An integrated framework and a software implementation are developed in order to realize the research objective. The integrated approach is called 'Enhanced Design For Assembly' (EDFA) and consists of the principles adopted from the Hitachi AEM, virtual manufacturing system and assembly principles and guidelines. From the case studies that have been carried out using the EDFA approach the results showed that it can minimize assembly complexity, reduce the overall assembly cost and reduce the number of part and component in product development and improvement. The software "EDFA' is easy to use and helps the designer's work in product design development and improvement. The comparison of EDFA method with Boothroyd-Dewhurst shows the capability of producing good results.